2020
DOI: 10.1186/s43045-020-00069-2
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and anxiety symptoms, quality of sleep, and coping during the 2019 coronavirus disease pandemic in general population in Kashmir

Abstract: Background With uncertainty surrounding the 2019 coronavirus disease pandemic, there is no knowledge of the psychological impact of this pandemic on the general public from Kashmir. We aimed to understand the psychological impact in the form of depressive symptoms, anxiety symptoms, quality of sleep, and coping during this pandemic. Methods This cross-sectional study was conducted using social networking sites. The questionnaire meant for this study was sent as a link to a respondent. Initial part of questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…A total of 250 studies [285 subgroups, i.e., multiple populations, multiple tools, or multiple data points] comprising 493,475 participants from 49 countries were included in the analyses [ [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [10...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 250 studies [285 subgroups, i.e., multiple populations, multiple tools, or multiple data points] comprising 493,475 participants from 49 countries were included in the analyses [ [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [10...…”
Section: Resultsmentioning
confidence: 99%
“… PSQI, ISI 7 35 Bezerra et al, 2020 [ 77 ] Brazil Yes General Population Cross-sectional design, N = 3836, Female = 73.5%, Age = 18-7 years. SD 6 36 Bhat et al, 2020 [ 78 ] India No General Population Cross-sectional design, N = 264, Female = 27.7%, Age = 18-60 years. PSQI 8 37 Bigalke et al, 2020 [ 79 ] USA Yes General Population Cross-sectional design, N = 103, Female = 59%, Age = 38 years.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding, we surmise that the fear and stress associated with COVID-19 may be one of the major reasons contributing to the high prevalence of sleep problems. More specifically, social media and news channels have continuously routinely reported on daily deaths and on the number of cumulative infected cases of COVID-19 both at the national and global scales, and such intensive media exposure is likely to generate the anxiety and stress 2020 China April 25-May 9, 2020 no cross-sectional Wang (Wang, Xie et al, 2020) 2020 China January 30-February 7, 2020 no cross-sectional Hu (Giardino et al, 2020) 2020 China March 7-24, 2020 no cross-sectional Yang (Xiao et al, 2020) 2020 China March 5-14, 2020 no cross-sectional Gualano (Gualano et al, 2020) 2020 Italy April 19 and May 3, 2020 yes cross-sectional Pieh (Pieh et al, 2020) 2020 Austria April 15-30, 2020 yes cross-sectional Zhuo (Zhuo et al, 2020) 2020 China March 2020 no cross-sectional Wang (Ren et al, 2020) 2020 China February 2 and 3, 2020 no cross-sectional Shi (Shi et al, 2020) 2020 China February 28-March 11, 2020 no cross-sectional Lai (Lai, Ma et al, 2020) 2020 China January 29-February 3, 2020 no cross-sectional Zhou 2020 China March 24-3 April, 2020 no cross-sectional Zhang (Zhang, Xu et al, 2020) 2020 China January 25 and March 15 no retrospective cohort Wasim (Wasim et al, 2020) 2020 Pakistan May 20-June 3, 2020 no cross-sectional Sharma (Sharma et al, 2020) 2020 India 0 no cross-sectional Tiete (Tiete et al, 2020) 2021 Belgium April 17-May 25, 2020 no cross-sectional Franceschini (Franceschini et al, 2020) 2020 Italy March 10-May 4, 2020 yes cross-sectional Bhat (Bhat et al, 2020) 2020 Kashmir April 4-10, 2020 no cross-sectional Liu (Liu et al, 2020) 2021 China February 1-10, 2020 no cross-sectional Alamrawy (Alamrawy et al, 2021) 2021 Egypt July 2-23, 2020 no cross-sectional Akıncı (Akıncı & Başar, 2021) 2021 Turkey April and May, 2020 no cross-sectional Barua (Barua et al, 2020) 2021 Bangladesh April 1-May 30, 2020 no cross-sectional Fidanci (Fidanci et al, 2020) 2020 Turkey May 2020 no cross-sectional Gu (Peng et al, 2020) 2020 China February 15-22, 2020 no cross-sectional Almater (Almater et al, 2020) 2020 Saudi Arabia March 28-April 4, 2020 no cross-sectional Khoury (Khoury et al, 2021) 2021 Canada June 3 and July 31, 2020 no cross-sectional Wang …”
Section: Discussionmentioning
confidence: 99%